Context-dependent associations between heterozygosity and immune variation in a wild carnivore. (December 2015) - Brock, Patrick; Goodman, Simon; Hall, Ailsa; Cruz, Marilyn; Acevedo-Whitehouse, Karina
Abstract Background A multitude of correlations between heterozygosity and fitness proxies associated with disease have been reported from wild populations, but the genetic basis of these associations is unresolved. We used a longitudinal dataset on wild Galapagos sea lions (Zalophus wollebaeki ) to develop a relatively new perspective on this problem, by testing for associations between heterozygosity and immune variation across age classes and between ecological contexts. Results Homozygosity by locus was negatively correlated with serum immunoglobulin G production in pups (0–3 months of age), suggesting that reduced genetic diversity has a detrimental influence on the early development of immune defence in the Galapagos sea lion. In addition, homozygosity by locus was positively correlated with total circulating leukocyte concentration in juveniles (6–24 months of age), but only in a colony subject to the anthropogenic environmental impacts of development, pollution and introduced species, which suggests that reduced genetic diversity influences mature immune system activity in circumstances of high antigen exposure. Conclusions These findings demonstrate the environmental context-dependency of the phenotypic expression of immune variation, which is implicit in the theory of ecoimmunology, but which has been rarely demonstrated in the wild. They also indicate that heterozygosity may be linked to the maintenance of heterogeneity in mammalian immune system development and response to infection, adding to the body of evidence on the nature of the mechanistic link between heterozygosity and fitness.